2016
DOI: 10.1002/wmh3.198
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a Cross-Cutting Issue in Food Security: The NuME Project and Quality Protein Maize in Ethiopia

Abstract: Gender research and gender empowerment, particularly through the increased participation of women in extension services and activities, are recommended components in development initiatives toward achieving gender equality, food security, and improved health in rural populations. Gender dynamics have been under-researched in the agricultural technology literature on Sub-Saharan Africa. This article contributes a gender-based analysis of the Nutritious Maize for Ethiopia (NuME) project, an initiative implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…As such, these interventions can inadvertently propagate vulnerability and inequity in adaptive capacity rather than reduce it. For example, in the case of agricultural interventions, men or maleheaded households are much more likely to adopt improved seeds, which are largely promoted to both increase household crop productivity as well as to help households cultivate climate-resilient crops (Uduji and Okolo-Obasi 2018, Fisher and Kandiwa 2014, O'Brien et al 2016, Theriault et al 2017, Lambrecht et al 2018. Women and men also often engage in different forest harvesting activities, and when men are often the main voices in forest management programs like REDD+ this can impact women's vulnerability by reducing their capacity to benefit from forest resources (Devkota and Mustalahti 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these interventions can inadvertently propagate vulnerability and inequity in adaptive capacity rather than reduce it. For example, in the case of agricultural interventions, men or maleheaded households are much more likely to adopt improved seeds, which are largely promoted to both increase household crop productivity as well as to help households cultivate climate-resilient crops (Uduji and Okolo-Obasi 2018, Fisher and Kandiwa 2014, O'Brien et al 2016, Theriault et al 2017, Lambrecht et al 2018. Women and men also often engage in different forest harvesting activities, and when men are often the main voices in forest management programs like REDD+ this can impact women's vulnerability by reducing their capacity to benefit from forest resources (Devkota and Mustalahti 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research from Malawi suggests that access to an input subsidy may reduce these barriers for women, if they are able to access the subsidy (Fisher and Kandiwa 2014). Likewise, research from Africa and South Asia has demonstrated that women are typically less likely than men to participate in initiatives promoting the use of improved seeds as a result of physical and cultural barriers to access as well as a lack of targeted extension services (Uduji and Okolo-Obasi 2018, Fisher and Kandiwa 2014, O'Brien et al 2016, Theriault et al 2017, Lambrecht et al 2018. One study from the Demographic Republic of the Congo did find, however, that women were much more likely to engage in the use of improved seeds when they were promoted by an extension service, as their cultivation was laborintensive but not as capital-intensive as fertilizer (Lambrecht et al 2018).…”
Section: Agricultural Technology Promotionmentioning
confidence: 99%
“…Smallholder agriculture is the economic mainstay of the 85 percent rural population of Ethiopia, where the average landholding size is less than 1 hectare. Gender relations and the gendered power dynamics between men and women affect participation and decision‐making processes across the agricultural continuum (O'Brien et al, ). This is especially evident in a patriarchal social hierarchy where ownership of resources and decision‐making power are disproportionately biased against women and in favor of men (O'Brien et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gender relations and the gendered power dynamics between men and women affect participation and decision‐making processes across the agricultural continuum (O'Brien et al, ). This is especially evident in a patriarchal social hierarchy where ownership of resources and decision‐making power are disproportionately biased against women and in favor of men (O'Brien et al, ). Women's empowerment, such as greater participation and voice over household/community decision making, would improve household food security and smallholder farm productivity (O'Brien et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation